Studi Etnobotani Pemanfaatan dan Pengolahan Tanaman Obat untuk Sapi Ternak: Studi Kasus Peternakan Ar-Rahman - Aisya Utami; Radhwa Nasywa Rizandia; Tri cahyanto; Afriansyah Fadillah (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2026)
This study describes the use of medicinal plants by Ar-Rahman Farm in Cileunyi District as part of local ethnoveterinary practices used to maintain livestock health. Ethnoveterinary knowledge represents traditional community experience in utilizing natural resources, particularly medicinal plants, for the prevention and treatment of animal diseases. The research employed a qualitative case study approach involving a single key informant selected based on knowledge and experience in livestock management. Data were collected through direct observation and in-depth interviews, then analyzed descriptively to identify plant species and their medicinal functions. The results identified seven medicinal plants commonly used to treat wounds, digestive disorders, fever, and loss of appetite in livestock. The plants included Piper betle, Psidium guajava, Zingiber officinale, and several species of Curcuma, which are prepared and administered using traditional methods. These findings demonstrate that local knowledge continues to play an important role in supporting livestock health management. Furthermore, the documented practices have the potential to contribute to ethnobotanical studies, sustainable livestock production, and future animal health research.